Enhancing Learning Quality and Students’ Moral Character through In-House Training for School Educators - Madya Giri Aditama; Utomo; Nurina Sawatuz Zuhro (Universitas 'Aisyiyah Bandung, 2026)
Improving learning quality and strengthening students’ moral character have become critical priorities for schools in responding to contemporary educational challenges, including rapid technological advancement, changing student behavior, and increasing demands for holistic education. Teachers and educational staff play a strategic role in creating meaningful learning experiences while fostering positive values and character development among students. This community service programme aimed to enhance the capacity of school educators through an In-House Training programme focused on improving learning quality and strengthening students’ moral character. The programme was conducted at a senior high school in Central Java, Indonesia, involving 33 participants consisting of teachers and educational staff. A participatory training approach was employed through expert lectures, interactive discussions, reflective activities, collaborative problem-solving, and action-planning sessions. Data were collected through observations, evaluation questionnaires, and reflective feedback forms, and were analyzed using descriptive quantitative and qualitative techniques. The findings revealed substantial improvements in participants’ understanding of innovative learning strategies, student engagement practices, character education integration, and collaborative school culture development. Participants also reported high levels of satisfaction with the programme and demonstrated strong intentions to implement the knowledge and strategies acquired during the training. Furthermore, the programme fostered collective commitment among school personnel to support sustainable educational improvement. It can be concluded that the In-House Training approach was effective in addressing the professional development needs of educators and educational staff while promoting a holistic educational environment that integrates academic excellence with students’ moral character development.